Bulbar dysfunction: An early presentation of congenital myasthenic syndrome in three infants - Khan, Arif (Medknow Publications & Media Pvt Ltd, 2011)
Congenital myasthenic syndromes are a group of rare genetic disorders affecting neuromuscular transmission. A high index of suspicion is required as clinical manifestations can be variable and nonspecific. Clinical phenotype includes arthrogryposis, respiratory crises, facial deformities, and weakness. With the availability of molecular genetics, this group of conditions can now be more clearly delineated and targeted treatment can be initiated. We describe three children who presented with bulbar difficulties and had Cholinergic receptor, nicotinic, and epsilon or receptor associated protein of the synapse mutations.